ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PERUSAHAAN (Studi Empiris pada Perusahaan Food & Beverages yang Terdaftar di BEI Tahun 2009 – 2013) - Untung Sriwidodo, Regina Christy Puspaningrum, Y.Djoko Suseno & (Universitas Slamet Riyadi, 2018)
High profit growth signifies a prosperity that every company wants to achieve. The purpose of this research was to analyze the significance of the influence of financial ratios consisting of current ratio, net profit margin, total assets turnover, debt to assets ratio and return on assets to the company's profit growth. The research population used data from food and beverage companies listed on the Indonesia Stock Exchange from 2009 to 2013. From 20 companies listed, 13 companies were taken as research sample, where they have complete financial statement information. Data analysis used classical assumption test, descriptive, static, multiple linear regression, t test, F test and coefficient of determination. The results showed that the five financial ratios partially and simultaneously have a significant effect on the profit growth. Thus, it can be concluded that financial ratios partially and simultaneously have a significant effect on the profit growth of food and beverages companies listed on the Stock Exchange from 2009 to 2013. Keywords: Profit Growth, Financial Ratio,Coefficient of Determination, Multiple Linear Regression, Classical Assumption Test.